Which Definition of Upper Rectal Cancer Is Optimal in Selecting Stage II or III Rectal Cancer Patients to Avoid Postoperative Adjuvant Radiation? - Gao, Xian Hua; Zhai, Bai Zhi; Li, Juan; Kabemba, Jean Luc Tshibangu; Gong, Hai Feng; Bai, Chen Guang; Liu, Ming Lu; Zhang, Shao Ting; Shen, Fu; Liu, Lian Jie; Zhang, Wei (Frontiers in Oncology, 2021)
Background: In most guidelines, upper rectal cancers (URC) are not recommended to take neoadjuvant or adjuvant radiation. However, the definitions of URC vary greatly. Five definitions had been commonly used to define URC: (1) >10cm from the anal verge by MRI; (2) >12cm from the anal verge by MRI; (3) >10cm from the anal verge by colonoscopy; (4) >12cm from the anal verge by colonoscopy; (5) above the anterior peritoneal reflection (APR). We hypothesized that the fifth definition is optimal to identify patients with rectal cancer to avoid adjuvant radiation. Methods: The data of stage II/III rectal cancer patients who underwent radical surgery without preoperative chemoradiotherapy were retrospectively reviewed. The height of the APR was measured, and compared with the tumor height measured by digital rectal examination (DRE), MRI and colonoscopy. The five definitions were compared in terms of prediction of local recurrence, survival, and percentages of patients requiring radiation. Results: A total of 576 patients were included, with the intraoperative location of 222 and 354 tumors being above and straddle/below the APR, respectively. The median distance of the APR from anal verge (height of APR) as measured by MRI was 8.7 (range: 4.5-14.3) cm. The height of APR positively correlated with body height (r=0.862, P<0.001). The accuracy of the MRI in determining the tumor location with respect to the APR was 92.1%. Rectal cancer above the APR had a significantly lower incidence of local recurrence than those straddle/below the APR (P=0.042). For those above the APR, there was no significant difference in local recurrence between the radiation and no-radiation group. Multivariate analyses showed that tumor location regarding APR was an independent risk factor for LRFS. Tumor height as measured by DRE, MRI and colonoscopy were not related with survival outcomes. Fewer rectal cancer patients required adjuvant radiation using the definition by the APR, compared with other four definitions based on a numerical tumor height measured by MRI and colonoscopy. Conclusions: The definition of URC as rectal tumor above the APR, might be the optimal definition to select patients with stage II/III rectal cancer to avoid postoperative adjuvant radiation.